Character Transformation Through the Implementation of the Radec Learning Model at the Elementary School Level - Suryana, Nana; Sopandi, Wahyu; Budimansyah, Dasim; Ruyadi, Yadi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to explore character transformation through the implementation of the RADEC (Read, Answer, Discuss, Explain, Create) learning model at the elementary school level. The research was conducted in Cluster III, Pagerageung District, Tasikmalaya Regency. A qualitative approach with a case study design was employed, involving 40 teachers as participants. The research data consisted of classroom observation results, in-depth interview transcripts with teachers, and lesson planning and evaluation documents related to the RADEC model. Data were collected through observation, in-depth interviews, and documentation studies. The data were analyzed thematically through stages of data reduction, data display, and inductive conclusion drawing to identify patterns in the implementation of the RADEC model and its impact on students’ character development. The findings indicate that the RADEC model can be effectively applied in classrooms, although variations in implementation exist. This model has proven effective in enhancing student character, particularly in aspects of cooperation, discipline, responsibility, creativity, and self-confidence. However, its application faces challenges such as limited time and inadequate facilities. This study recommends further teacher training and the improvement of learning infrastructure to support the optimal implementation of the RADEC model.